The "Brain Stress Timing" phenomenon and other misinterpretations of randomized clinical trial on aneurysmal subarachnoid hemorrhage - Martinez-Perez, Rafael (2019)
Clipping and coiling are currently the two alternatives in treatment of ruptured cerebral aneurysms. In spite of some meritorious analysis, further discussion is helpful to understand the actual state of art. Retreatment and rebleeding rates clearly favors clipping, although short-term functional outcome seems to be beneficial for clipping, while this different is not such if we perform the comparison at a longer follow up. Long-term follow ups and cost analysis are mandatory to have a clear view of the current picture in treatment of subarachnoid hemorrhage. Treatment strategy should be made by a multi-disciplinary team in accredited centers with proficient experience in both techniques.